The late quaternary cover bed stratigraphy and tephrochronology of north-eastern and central Taranaki, New Zealand : a thesis presented in partial fulfullment of the requirements for the degree of Doctor of philosophy in soil science at Massey University, Palmerston North, New Zealand - Alloway, Brent Victor (Massey University, 1989)
This study involved the recognition and description of tephra, lahar and debris avalanche deposits generated from activity centred at Egmont Volcano over the last c.l30kyrs B.P. Stratigraphic relationships between the various cover bed deposits of north-eastern and central Taranaki are discussed and their distributions mapped where possible. The stratigraphic record indicates that tephra emission and lahar inundation are typical, recurring features of Egmont Volcano. Average periodicity for moderate to major sized eruptions (>107m3) may be as frequent as, one every 250 years. Tephras from Egmont Volcano have been correlated to both the adjacent Wanganui and Waikato districts. Six rhyolitic tephras erupted from the Central North Island have been identified in Taranaki and are especially valuable as widespread time planes within the andesitic cover bed succession. At least thirteen lahars are shown to have been deposited over extensive areas of the ring plain during the last 22.5 kyrs B.P. Many of these lahars became channelised within stream and river catchments to extend to the North Taranaki coastline. Partial or complete collapse of Egmont Volcano at c.23kyrs and much earlier at c.100kyrs B.P. generated large volumed, debris avalanches that spread principally over a wide north-eastern to south-eastern arc. The resulting deposits are characterised by extensive areas of mounds now deeply buried by a younger late Pleistocene and Holocene tephra mantle. The stratigraphy of an alternating sequence of reddish (S-units) and yellowish (L-units) medial beds was also investigated. Generally their thinning pattern is similar to that of coarse ash and lapilli suggesting tephric origin.The thinning pattern of L-units however, is occasionally interrupted by localised overthickening and indicates localised aeolian deposition during cool to cold climatic periods. The biostratigraphic record constructed from pollen examinations support the climatic interpretations made from the medial stratigraphy. The measurement of quartz content in medial units is shown to be a particularly useful parameter for assessing past climatic conditions. Two peaks in quartz influx were recorded and correlated to the full-glacial periods of oxygen isotope stages 2 and 4. Forming the North Taranaki coastal plain are five uplifted marine terraces, that provide a c.0.45 Ma record of successive sea level oscillations with moderate to low rates of crustal deformation. The present extent of these terraces is related to lahar deposits within their cover beds which have repeatedly advanced the coastline and retarded coastal erosion.
Keywords: Mt Egmont; Mount Egmont; Mt Taranaki; Mount Taranaki; Tephra; Lahar; Stratigraphy; Marine terraces